A case study of AstraZeneca’s omeprazole/esomeprazole chiral switch strategy - Piñeiro, Federico Jesús (2022)
Introduction/Objective: To describe the chiral switch, an evergreening strategy used by AstraZeneca to position enantiopure esomeprazole as the new proton pump inhibitor market leader, displacing its predecessor omeprazole.Methodology: A four-stage systematic review which included: a preliminary review, bibliographic review using databases, classification of the body of literature, and content analysis.Results: Using different legal and commercial strategies, such as patent thickets and aggressive publicity campaigns, AstraZeneca transferred consumer loyalty from their successful omeprazole to esomeprazole, its new and more expensive patent protected product which has the same therapeutic value as its predecessor. This chiral switch allowed AstraZeneca to maintain monopoly prices, which increased the financial burden experienced by consumers and payors and may have also had a negative impact on access to the medication.Conclusions: This case study exemplifies how the current patent system, including patent thickets, can be used to enhance the profits of pharmaceutical companies while stalling innovation and placing undue financial burdens on the consumer.